E-cadherin prolongs the moment for interaction between intestinal stem cell and its progenitor cell to ensure Notch signaling in adult Drosophila midgut. - Maeda, K.; Takemura, M.; Umemori, M.; Adachi-Yamada, T. (Genes to cells : devoted to molecular & cellular mechanisms, 2008)
Intestinal stem cells (ISCs) are required for maintenance of the proper cell composition in the adult intestine. To ensure permanent recruitment of newly differentiated cells, the ISC undergoes asymmetric cell division that generates an ISC itself and a progenitor cell. In the Drosophila midgut, cell fate for the absorptive cell is determined by Notch (N) signal in the progenitor cells that receive a ligand Delta (Dl) produced by the ISCs. Although most of the ISCs and progenitor cells are distantly located, they should retain their attachment when N is activated because the Dl-N interaction requires cell adhesion. Furthermore, N cannot be activated before completion of cell division. Thus, the moment after cell division and before cell separation should be prolonged for certain N activation, although the mechanism for this remains unclear. Here, we demonstrate that E-cadherin (E-cad) is required for stable attachment between the two cells. When E-cad does not function, N is not activated and cell differentiation is attenuated. We also show that the ISC tumor by N inactivation is assisted by a defect in E-cad down-regulation. These findings reveal one of the normal N functions used to inhibit tumorigenesis through lowering of E-cad for proper midgut cell turnover.